EVALUASI KINERJA RUANG PEJALAN KAKI DI JALAN MALIOBORO YOGYAKARTA - Pradipto, Ranar; Kharis, Zulfikar; Wicaksono, Y.I.; Indriastuti, Amelia Kusuma (Jurnal Karya Teknik Sipil, 2014)
Malioboro as one of  most tourism destination in Yogyakarta has a large number of visitors.  More than 4,000 people visiting  Malioboro area per day. The number of visitors at  pedestrian area  resulting inability Malioboro to receive such capacity. For  resolve these problems,  an  evaluation  of the service is needed more pedestrian capacity  (level of service). so that visitors will know about Malioboro growth in the future. and  The reference can being recommendation  as handling problems that occur at Malioboro street. The survey  undertaken are pedestrian  survey. Pedestrian survey is aimed to obtain  number of tourists data  in Malioboro pedestrians . The survey were conducted in three-point locations who can represent characters of  Malioboro, in front of the Hotel Inna Garuda,  Malioboro Mall and  Sami Jaya. The analysis is carried out to the HCM 2000. The result  of pedestrian survey are  Level of Service value. Base on the parking income data the growth rate of pedestrian area is about 5.2% . in the next five years the Level of Service will be bad with Level of service D. this mean there is a crowded situation in pedestrian area. overcome these problems we need  rearrangement pedestrian area  along Malioboro street  and make a planning analysis to resolve this issue hopefully can accommodating  Malioboro area for next 5 years in Pedestrian area with  Level of Service (LOS) B.